2002
DOI: 10.1074/jbc.m109179200
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclin-dependent Kinase Inhibitor p21WAF1/Cip1 Is an Antiestrogen-regulated Inhibitor of Cdk4 in Human Breast Cancer Cells

Abstract: The MCF-7 cell line is a model of estrogen-dependent, antiestrogen-sensitive human breast cancer. Antiestrogen treatment of MCF-7 cells causes dramatic decreases in both Cdk4 and Cdk2 activities, which leads to a G 1 phase cell cycle arrest. In this report, we investigate the mechanism(s) by which Cdk4 activity is regulated in MCF-7 cells. Through time course analysis, we demonstrate that changes in Cdk4 activity in response to estrogen or antiestrogen treatment do not correlate directly with cyclin D1 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…cells and that promoting the formation of p21-free CDK complexes is sufficient for CDK activation and cell cycle progression (16,17,51,53). Together, these results suggest that a key mechanism by which c-Myc promotes proliferation of breast cancer cells in the presence of ICI is by decreasing p21 levels.…”
Section: P21 Is Targeted In Myc-induced Proliferation Of Mcf-7 Cellssupporting
confidence: 53%
See 3 more Smart Citations
“…cells and that promoting the formation of p21-free CDK complexes is sufficient for CDK activation and cell cycle progression (16,17,51,53). Together, these results suggest that a key mechanism by which c-Myc promotes proliferation of breast cancer cells in the presence of ICI is by decreasing p21 levels.…”
Section: P21 Is Targeted In Myc-induced Proliferation Of Mcf-7 Cellssupporting
confidence: 53%
“…Our results with stable MCF-7 derivatives indicated that c-Myc can repress p21 expression but did not directly address whether the previously reported (18,22,51) decreases in p21 in response to E2 treatment are mediated via c-Myc. We therefore used RNA interference to demonstrate that c-Myc expression is required for the E2-mediated decrease in p21 in MCF-7 cells and thus identified c-Myc as the first direct link between E2 and p21 in breast cancer cells.…”
Section: P21 Is Targeted In Myc-induced Proliferation Of Mcf-7 Cellsmentioning
confidence: 66%
See 2 more Smart Citations
“…Modulation of p21 functions depends on its final concentration in cells; lower levels of p21 initially promote cell cycle progression by stimulation of cyclin-CDK assembly (52,53), whereas higher levels will inhibit cyclin-CDK activity. Our data suggest that only when there are no p21-free cyclin A-CDK2 complexes will p21 interact with PCNA.…”
Section: P21 Down-regulation Is Required For Replication Restartmentioning
confidence: 99%